Pengaruh Kualitas Produk Dalam Perspektif Islam Terhadap Volume Penjualan di Toko Gia Toys Grong-Grong Pidie - Hasballah, Ibrahim (Yayasan Madinah Al-Aziziyah, 2023)
In the current era of globalization, rapid developments in the toys sector have led to increasingly fierce business competition. This condition requires all entrepreneurs in the world engaged in toy shops to improve and develop their products in order to win the competition. Gia Toys store is a store that sells various types of toys needed such as cars, rubber horses, dolls, rackets, baby bites and other toys. The problem in this study is how the influence of product quality in an Islamic perspective on sales volume at Gia Toys Pidie Store. The method used is descriptive qualitative method. This research is categorized as field research through primary data obtained from field research and secondary data obtained from library research. The results of this research or conclusion explain that. Product quality in an Islamic perspective can also have an impact on increasing sales volume at the Gia Toys store which is based on honesty, transparency, and adherence to quality standards.